2010
DOI: 10.1093/rheumatology/keq395
|View full text |Cite
|
Sign up to set email alerts
|

Microangiopathic haemolytic anaemia resembling thrombotic thrombocytopenic purpura in systemic lupus erythematosus: the role of ADAMTS13

Abstract: Thrombotic thrombocytopenic purpura (TTP) is a rare but frequently fatal complication of SLE. It occurs in the context of both active and inactive lupus and carries a worse overall prognosis than idiopathic acquired TTP. Recent advances in the knowledge and treatment of TTP do not seem to have brought similar improvements in the management and outcome of TTP in SLE. The illumination of the role of the von Willebrand factor multimer protease, ADAMTS13 in idiopathic TTP continues to enhance our comprehension of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 31 publications
1
60
0
4
Order By: Relevance
“…Although TTP and SLE are different diseases, they may present as overlapping for each other although the association between them hasn't been well defined [4] . There are many hypotheses are being found to explain this association include abnormal endothelial activation, elevated levels of D-dimers, ADAMTS13-resistant von Willebrand Factor and defects in the complement system regulation [5] . SLE can be presented with symptoms resembling those of TTP making the differentiation very difficult, especially our patient didn't have any history or symptoms suggesting lupus before [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Although TTP and SLE are different diseases, they may present as overlapping for each other although the association between them hasn't been well defined [4] . There are many hypotheses are being found to explain this association include abnormal endothelial activation, elevated levels of D-dimers, ADAMTS13-resistant von Willebrand Factor and defects in the complement system regulation [5] . SLE can be presented with symptoms resembling those of TTP making the differentiation very difficult, especially our patient didn't have any history or symptoms suggesting lupus before [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Pero algunas poblaciones son más susceptibles de desarrollarla, incluyendo los pacientes con LES (1 a 4%) 9 .…”
Section: Algunos Aspectos Generales Sobre Púrpura Trombocitopénica Trunclassified
“…The mainstay of treatment in TTP is plasma exchange 1 7. Even with treatment, SLE-associated TTP was reported to have a higher mortality, 34–62.5%, compared to idiopathic TTP, which was about 20% mortality 1 4–6 8 9. Some small studies showed a benefit of adding other immunosuppressive agents in SLE-associated TTP 9.…”
Section: Introductionmentioning
confidence: 99%